Effect of Cold Stress on Photosynthetic Traits, Carbohydrates, Morphology, and Anatomy in Nine Cultivars of Stevia rebaudiana - Hajihashemi, Shokoofeh; Noedoost, Fariba; Geuns, Jan M. C.; Djalovic, Ivica; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2018)
Stevia rebaudiana Bertoni is a sweet medicinal herb that is cultivated worldwide. This study aimed to identify the genotypic responses and function of nine cultivars of Stevia rebaudiana (accession numbers 1 to 9 from the EUSTAS Stevia Gene Bank) to low temperature. Plants were grown in vitro and incubated under controlled conditions at 5°C or 25°C for one month. Cold stress significantly decreased the maximum quantum yield of photosystem II (Fv/Fm) in all cultivars, which was more pronounced in cultivars 5, 6, 8 and 9. The efficiency of photosystems I and II (PIABS) also declined in cold-stressed plants and was accompanied by reductions in net photosynthesis (PN), intercellular CO2 (Ci), water use efficiency (WUE), and chlorophyll a, chlorophyll b and carotenoid contents, more so in cultivars 5, 6, 8 and 9. Regardless of the downregulation of photosynthetic capacity, the cold stress increased water-soluble carbohydrates in all cultivars, which was accompanied by an increase in fresh leaf mass per area, more so in cultivars 5, 6, 8 and 9. Furthermore, cold stress increased the stomatal index and density, epidermal cell density, stem diameter, xylem vessel width, phloem tissue width and number of sclerenchyma in all cultivars. Even though the nine cultivars of S. rebaudiana had lower PS II efficiencies at low temperatures, the increase in carbohydrates and leaf mass suggests that damage in PSII is not responsible for the reduction in its efficiency.